2022
DOI: 10.1177/07356331211070975
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Among ICT-Related Psychological Factors, School Contextual Factors and Secondary Students’ Reading Performance: A Multilevel Analysis Across 47 Economies

Abstract: Evolving information and communication technology (ICT) reshapes people’s reading activities by popularizing digital reading. Past studies focused on the relationships between students’ frequency of ICT use and reading performance but neglected the possible interrelationships between students’ ICT-related psychological factors, school contextual factors and reading performance. This study applied the Self-determination Theory (SDT) to explore the relationships between students’ ICT-related psychological factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…On the one hand, schools are recommended to build a competence-supportive environment, for instance, to give positive feedback (Deci & Ryan, 2000), which could help satisfy students’ basic psychological needs for competence (Areepattamannil & Santos, 2019). Moreover, providing more quality-oriented support for technology-integrated instruction at school are likely to strengthen the positive effects of ICT perceived competence on students’ digital reading performance (Xiao & Hew, 2022). On the other hand, positive attitudes can derive from school use as well as from home use (Petko et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, schools are recommended to build a competence-supportive environment, for instance, to give positive feedback (Deci & Ryan, 2000), which could help satisfy students’ basic psychological needs for competence (Areepattamannil & Santos, 2019). Moreover, providing more quality-oriented support for technology-integrated instruction at school are likely to strengthen the positive effects of ICT perceived competence on students’ digital reading performance (Xiao & Hew, 2022). On the other hand, positive attitudes can derive from school use as well as from home use (Petko et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Lim and Jung (2019) found that students’ self-confidence in completing high-level ICT tasks was positively related to their digital reading performance. Similarly, studies utilizing the PISA 2015 (Hu et al, 2018) and PISA 2018 database (Xiao & Hew, 2022) revealed that students who perceived themselves as competent in using ICT performed better in digital reading tasks. Moreover, when students perceive ICT as useful but uncontrollable, their performance in digital reading assessment deteriorates (Naumann & Saelzer, 2017).…”
Section: Literature Reviewmentioning
confidence: 96%